Calcium and Vitamin D Serum Level of Stunting and Severe Stunting Children Aged 12-23 Months in the Pauh Health Center, Padang City - Nice Rachmawati Masnadi; Finny Fitry Yani; Delmi Sulastri; Firdawati Firdawati (Green Publisher Indonesia, 2025)
Stunting remains a significant public health challenge, particularly in developing countries. Vitamin D and calcium play crucial roles in linear growth and bone mineralization during early childhood. This study aimed to analyze the levels of serum vitamin D and calcium in stunted and severely stunted children aged 12–23 months in the working area of Pauh Health Center, Padang City, West Sumatra. This cross-sectional analytical study was conducted from February to May 2025, involving 43 children aged 12–23 months (33 stunted and 10 severely stunted). Data were analyzed using the chi-square test and independent-samples t-test. Most children exhibited hypovitaminosis D (62.7%), with 9.3% deficiency and 53.4% insufficiency. Serum calcium levels were predominantly normal (85.1%). No significant differences were found in vitamin D levels (p > 0.05) or calcium levels (p > 0.05) between stunted and severely stunted children. The mean vitamin D level was 12.14 ± 1.97 ng/mL in stunted children and 12.16 ± 1.63 ng/mL in severely stunted children. The mean serum calcium levels were 9.14 ± 1.97 mg/dL in stunted children and 9.16 ± 1.63 mg/dL in severely stunted children, respectively. Despite the high prevalence of vitamin D insufficiency, there were no significant differences in serum vitamin D and calcium levels between stunted and severely stunted children aged 12–23 months. The body's homeostatic mechanisms maintain normal serum calcium levels despite low vitamin D status, potentially at the expense of bone density. Further research is needed to identify other contributing factors to stunting severity.